ANALISIS PENGARUH PERTUMBUHAN EKONOMI TERHADAP KEMISKINAN DI INDONESIA - Lisa Nansadiqa (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2024)
This Research conducted to see the effect of economic growth on proverty in Indonesia, the data used is secondary data forn the Wirld Bank, Bank Indonesia and the Central Statistics Agency in 1990-2022.The analysis menthid used in thi research is the VAR (Vector Autoregressive) method. This model can explain short, medium and long term behavior. The results of research on the Impulse Response Function Show that the GDP Variable is related to proverty. States that in the short term there is an of the GDP Variable is related to proverty. States that in the short term is an effect of the shock caused by GDP on proverty, wile in the medium term or long term there is no effect of the shock caused by GDP on proverty.